Tinjauan Teknik Vokal Gaya Dendang dalam Menyanyikan Lagu Minyak Habih Samba Tak Lamak Ciptaan David Iztambul - Iqbal Syahrul Ramadhan; Yos Sudarman (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The aim of this research is to review the singing style vocal technique in singing the song Minyak Habih Samba Tak Lamak created by David Iztambul. This research uses descriptive qualitative research which looks at how singing style vocal techniques are used when research is carried out in the field and presents the results as they are. The informants in this research were David Iztambul himself and his colleagues. Data collection techniques use observation, interviews and documentation methods which will then be analyzed later to reach a conclusion. Based on the results of this research, the writer can conclude that the use of the singing style vocal technique used in the song Minyak Habih Samba Tak Lamak by David Iztambul consists of 4 types as follows: (1) The singing style vocal technique with chest and throat breathing which has a purpose. so that the song is sung in one breath that cannot be interrupted and that there are no mistakes in singing this song. (2) This singing style vocal technique uses articulation where there are no rules regarding mouth position as is done in basic vocal techniques. The most important thing is that the pronunciation sounds beautiful, melodious and has more taste. (3) Singing style vocal technique with resonance, this is because the oil habih samba songs don't use low notes for a long time, which can be done using techniques that use the head, throat, nose and chest breathing. (4) This singing style vocal technique usually uses the Garinyiak darek singing technique because the song Minyak Habih Samba Tak Lamak contains parasaian singing or singing. The melody is slow and non-rhythmic, meaning it is not bound by tempo, but there are also melodies that are bound by an irregular tempo. This is because the song Minyak Habih Samba Tak Lamak itself tells the feelings felt by a person based on their environment which is sung slowly.